Values, food and bags: A study of consumption decisions in a laboratory supermarket - Tim Kasser; Astrid Matthey (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We study the relation between people's personal values and environmentally friendly consumption behavior. We first assessed subjects' personal values using the Aspiration Index. Then subjects participated in a laboratory supermarket offering organic and conventional food products and different kinds of bags. The results suggest that subjects' personal values are poor predictors of their ecologically-relevant consumption behavior. However, we find that subjects who spontaneously reflected upon power values made less ecologically sustainable consumption decisions than did those who reflected on universalism values. We discuss methodological differences as possible reasons for variations between our results and those of earlier studies.
Keywords: D12; Q31; Q56; 330; conservation (ecological behavior); consumer behavior; values